2019
DOI: 10.1177/2050313x19833254
|View full text |Cite
|
Sign up to set email alerts
|

The use of clozapine and clonazepam co-administration in the treatment of a severe tardive dyskinesia: A case report

Abstract: This is a case report of a patient who was treated with clozapine and clonazepam after he developed neuroleptic-induced tardive dyskinesia following treatment for schizophrenia. There are reports of clozapine treatment itself causing tardive dyskinesia; however, more reports have shown clozapine’s benefit for patients with neuroleptic-induced tardive dyskinesia. This is a case report of a patient with neuroleptic-induced tardive dyskinesia who benefitted from clozapine treatment with adjuvant use of clonazepam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…For patients with schizophrenia, CLZ is sometimes combined with CLNAZ, and the combination of the two can also help prevent the occurrence of tardive dyskinesia (TD) ( 23 ). In addition, some studies have also shown that increasing the use of CLNAZ can help improve the efficacy of CLZ and relieve anxiety symptoms in patients with schizophrenia ( 24 ). However, in the study conducted by Jiang P, they found that the combination of CLNAZ and CLZ can cause changes in blood CLZ and N-CLZ concentrations, and patients must increase the dose of CLZ to achieve satisfactory results ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with schizophrenia, CLZ is sometimes combined with CLNAZ, and the combination of the two can also help prevent the occurrence of tardive dyskinesia (TD) ( 23 ). In addition, some studies have also shown that increasing the use of CLNAZ can help improve the efficacy of CLZ and relieve anxiety symptoms in patients with schizophrenia ( 24 ). However, in the study conducted by Jiang P, they found that the combination of CLNAZ and CLZ can cause changes in blood CLZ and N-CLZ concentrations, and patients must increase the dose of CLZ to achieve satisfactory results ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Although clozapine monotherapy seems to be effective in terms of improving the movements associated with tardive dystonia, 19 some reports recommend the use of clozapine alongside other medications such as clonazepam. 17 In addition, there are studies indicating that clozapine can also cause tardive dyskinesia. 20 In conclusion, as evidenced by the improvement experienced by our patient, clozapine monotherapy could be a valuable agent for the treatment of TM and other TS in patients diagnosed with schizophrenia.…”
Section: Tardive Myoclonus Responsive To Clozapine Misdiagnosed As Re...mentioning
confidence: 99%
“…Although the mechanism behind clozapine's efficacy in relation to the treatment of TS is not yet fully understood, it has been suggested that clozapine works by acting on the changes that are induced in the brain's striatal system by the prolonged blockade of dopamine receptors as a result of the long-term use of antipsychotic medications 17,18 . Although clozapine monotherapy seems to be effective in terms of improving the movements associated with tardive dystonia, 19 some reports recommend the use of clozapine alongside other medications such as clonazepam 17 . In addition, there are studies indicating that clozapine can also cause tardive dyskinesia 20 …”
mentioning
confidence: 99%
“…Doctors tried to discontinue the current treatment and introduced the following drugs gradually: olanzapine, clozapine and clonazepam. This was the use of clozapine at a dose of 500 mg / day and clonazepam at a dose of 4 mg / day that gave a noticeable improvement, and the dyskinetic movements almost completely disappeared [8].…”
Section: Dyskinesia and Neurolepticsmentioning
confidence: 99%
“…Lekarze podjęli próbę odstawienia dotychczasowego leczenia i włączenia stopniowo następujących leków: olanzapiny, klozapiny oraz klonazepamu. To właśnie zastosowanie klozapiny w dawce 500mg/dobę oraz klonazepamu w dawce 4mg/dobę dało zauważalną poprawę, a ruchy dyskinetyczne prawie całkowicie zniknęły [8].…”
Section: Dyskinezy a Neuroleptykiunclassified